UPAYA GURU FIQIH DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Muhammad Fathuroji (UNISAN JURNAL, 2024)
The purpose of this study was to identify teacher aspirations in enhancing learning the The point of this examination is to decide educators' endeavors to expand understudies' learning inspiration in fiqh subjects at Assuryaniyah Islamic Center School, Bekasi City at PT Assuryaniyah Islamic Center School, Bekasi City. This exploration utilizes a subjective methodology with a contextual investigation and single case plan. Information assortment utilizes interview, perception and documentation strategies. Information examination strategies utilize illustrative investigation, intuitive examination models. This is finished to confirm the accuracy of the information triangulation data. The aftereffects of the exploration show that the educator's endeavors to build understudies' learning inspiration in fiqh subjects are through educator endeavors in expanding understudies' learning inspiration in fiqh subjects at Assuryaniyah Islamic Center School, Bekasi City. The aftereffects of the examination show that the educator's endeavors increment understudy inspiration in learning fiqh subjects by saying thank you, giving gifts, testing, and rebuffing. Members' Learning Inspiration to support the members, understudies of Assuryaniyah Islamic Center School, Bekasi City, fiqh subjects should be kept up with. Understudies have marks of endlessly want to finish inspiration and advancing necessities, which are past expectations and desires for what's in store. Factors that impact middle school understudies' learning inspiration. Islam Assuryaniyah Bekasi City The subject of fiqh is an intrinsic calculate the self-inspiration of these understudies. Outside factors that come from the understudy's current circumstance, like parental inspiration and the climate